Heat and Solvent Resistant Electrospun Polybenzoxazole Nanofibers from Methoxy-Containing Polyaramide. (28th December 2010) - Duan, Gaigai; Jiang, Shaohua; Chen, Shuiliang; Hou, Haoqing
Abstract : Polybenzoxazole (PBO) nanofibers were prepared via electrospinning and thermal conversion from its precursor, methoxy-containing polyaramide (MeO-PA). The MeO-PA was synthesized from low-cost monomers. The structures and properties of polymers (MeO-PA and PBO) were characterized by FT-IR, TGA, DSC, OPM, SEM, and so forth. It was found that the PBO nanofibers had a diameter ranging from 300 nm to 350 nm. The PBO nanofiber mats with high porosity provided a promising prospect in high-temperature filter materials, heat insulation materials, and high-temperature protection materials for its outstanding heat and solvent resistance and in preparing carbon nanofibers for its high char yield percentage.